Intellectual security and its impact on the psychological compatibility of the houswife - Alya (Journal of Human Sciences, 2020)
The main objective of this research is to study the relationship between intellectual security and its impact on the psychological compatibility of the heads of households of the research sample. The research tools included the general data form, intellectual security questionnaire, psychological compatibility questionnaire (researcher preparation), and the research followed descriptive and analytical method. The results of the research found that there are statistically significant differences in the intellectual security according to the study variables in favor of higher educational level of wife and older, wife work, the number of family members less and high monthly income. In favor of higher educational level of wife and older, wife work, less family members and high monthly income, There was a positive correlation correlation statistically significant between the themes of intellectual security and axes of psychological compatibility, and the educational level of the wife was the most influential factor in the rate of participation in the wife’s intellectual security by 80.1%, and educational level is also the most influential factor in the rate of participation in psychological compatibility by 90.2%, and the relative weight of the axes of intellectual security was logical thinking and then moderation and moderation, and the relative weight of the axes of psychological compatibility was self-confidence, then social consensus, followed by emotional balance, and finally self-acceptance.